BODIPY-Based Fluorescent Probes for Selective Visualization of Endogenous Hypochlorous Acid in Living Cells via Triazolopyridine Formation - Peraya Hiranmartsuwan; Sirilak Wangngae; Jukkrit Nootem; Anyanee Kamkaew; Rathawat Daengngern; Worawat Wattanathana; Kantapat Chansaenpak (My University, 2022)
In this work, the two pyridylhydrazone-tethered BODIPY compounds (2 and 3) were synthesized. These compounds aimed to detect hypochlorous acid (HOCl) species via cyclic triazolopyridine formation. The open forms and the resulting cyclic forms of BODIPYs (2, 3, 4, and 5) were fully characterized by nuclear magnetic resonance, mass spectrometry, infrared spectroscopy, and single-crystal X-ray diffraction. These two probes can selectively detect HOCl through a fluorescence turn-on mechanism with the limit of detections of 0.21 µM and 0.77 µM for compounds 2 and 3, respectively. This fluorescence enhancement phenomenon could be the effect from C = N isomerization inhibition due to HOCl-triggered triazolopyridine formation. In cell imaging experiments, these compounds showed excellent biocompatibility toward RAW 264.7 murine live macrophage cells and greatly visualized endogenous HOCl in living cells stimulated with lipopolysaccharide.
Keywords: Hypochlorous acid; BODIPY; Molecular Sensors and Ion Detection